Expression, Purification, and Characterization of Ras Protein (BmRas1) from Bombyx mori. (29th March 2012) - Quan, Yanping; Liu, Guangqiang; Yu, Wei; Nie, Zuoming; Chen, Jian; Lv, Zhengbing; Zhang, Yaozhou
Abstract : The Ras subfamily is the member of small G proteins superfamily involved in cellular signal transduction. Activation of Ras signaling causes cell growth, differentiation, and survival. Bombyx mori Ras-like protein (BmRas1) may belong to the Ras subfamily. It contained an H-N-K-Ras-like domain. The BmRas1 mRNA consisted of 1459 bp. The open reading frame contained 579 bp, encoding 192 amino acids. The protein had such secondary structures as α -helices, extended strand, and random coil. BmRas1 was expressed successfully in E. coli BL21. The recombinant protein was purified with metal-chelating affinity chromatography. The GTPase activity of purified protein was determined by FeSO4 -(NH4 )2 MoO4 assay. The results showed that purified recombinant protein had intrinsic activity of GTPase. High titer polyclonal antibodies were generated by New Zealand rabbit immunized with purified protein. The gene expression features of BmRas1 at different stages and in different organs of the fifth instar larvae were analyzed by Western blot. The results showed that BmRas1 was expressed highly in three development stages including egg, pupae, and adult, but low expression in larva. BmRas1 was expressed in these tissues including head, malpighian tubule, genital gland, and silk gland. The purified recombinant protein would be utilized to further function studies of BmRas1.